Hybrid-type generalized multivalued vector complementarity problems - Agarwal, R.P.; Ahmad, M.K.; Salahuddin (Український математичний журнал, 2013)
We introduce a new type of generalized multivalued vector complementarity problems with moving pointed cone. We discuss the existence results for generalized multivalued vector complementarity problems under inclusive assumptions and obtain results on the equivalence between the generalized multivalued vector complementarity problems and the generalized multivalued vector variational inequality problems. Введено новий тип узагальнених багатозначних векторних задач доповнюваностi з рухомим загостреним конусом. Розглянуто питання про iснування розв’язкiв узагальнених багатозначних векторних задач доповнюваностi при умовах включення та отримано результати щодо еквiвалентностi мiж узагальненими багатозначними векторними задачами доповнюваностi та узагальненими багатозначними векторними задачами для варiацiйних нерiвностей.